1999
DOI: 10.1152/advances.1999.277.6.s15
|View full text |Cite
|
Sign up to set email alerts
|

An inquiry-based teaching tool for understanding arterial blood pressure regulation and cardiovascular function.

Abstract: E ducators are placing a greater emphasis on the development of cooperative laboratory experiences that supplement the traditional lecture format. The new laboratory materials should encourage active learning, problem-solving, and inquiry-based approaches. To address these goals, we developed a laboratory exercise designed to introduce students to the hemodynamic variables (heart rate, stroke volume, total peripheral resistance, and compliance) that alter arterial pressure. For this experience, students are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…For examples of the problem-solving questions, readers are referred to two recent publications (4,16). The students were required to interpret, relate, and incorporate new information with existing knowledge and apply the new information to solve novel problems.…”
Section: Methodsmentioning
confidence: 99%
“…For examples of the problem-solving questions, readers are referred to two recent publications (4,16). The students were required to interpret, relate, and incorporate new information with existing knowledge and apply the new information to solve novel problems.…”
Section: Methodsmentioning
confidence: 99%
“…This is important because students must become life-time learners. The use of innovative educational games in the classroom can increase enthusiasm and reinforce previously presented didactic information (2,13,25,42,46). It is also a positive, interactive, alternative method of teaching and information sharing.…”
Section: What Curricular Changes Work?mentioning
confidence: 99%
“…To address these concerns, "virtual" experiments can be used. For example, virtual experiments have been designed to help students understand the theory and application of the electrocardiogram (1) and gastrointestinal (2), endocrine (46), and cardiovascular physiology (13). Virtual experiments expose students to experimental design and procedures; however, the data are provided so that the results can be analyzed and discussed despite the lack of equipment (47).…”
Section: What Curricular Changes Work?mentioning
confidence: 99%
“…8 With active learning strategies, visual learners were targeted by the presence of models and demonstrations. [14][15][16] In the same way, aural learners could be reached through discussion, 17,18 collaborative testing, 17,18 debate, 19 games, [20][21][22][23][24][25] and answering questions. 26 To achieve this goal, it became important to use active learning strategies, 27 Some investigators have reported an increase in learners' achievement with the use of simulations and games, and learners usually expressed positive feeling about the experiences.…”
Section: Discussionmentioning
confidence: 99%